Effect of halal and non-halal slaughtering methods on bacterial contamination of poultry meat - Idris, Lokman Hakim; Md Isa, Nur Mahiza; Mohd Tahir, Shahira; Busayo, Ibitoye E. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study was designed to investigate and compare the effect of halal (Islamic rules) and non-halal (non-Islamic rules) slaughtering methods on the quality characteristics of chicken. Ten village chickens weighing 0.9 - 1 kg of the same age and farm management were involved; five of them were slaughtered using the halal method, while the other five were slaughtered using the non-halal method by cutting only one side of the jugular vein and carotid artery. Bleeding time, death time, the volume of blood loss, microbial count of Standard Plate Count (SPC) and Coliform Plate Count (CPC) were determined immediately at and post-slaughtering. There was no significant difference in the microbial count of CPC between both slaughtering methods. Bleeding time, death time and SPC results for non-halal slaughtered chickens were significantly (p<0.05) higher than the halal slaughtered chickens, while the volume of blood lost was found significantly (p<0.05) lower for non-halal slaughtered chickens. These data suggested that non-halal slaughtered chickens could contain more residual blood in the meat that can lead to an increase in bacterial counts, consequently shortened shelf life.